Ofuji's disease in an immunocompetent patient successfully treated with dapsone - Gopikrishnan Anjaneyan (Indian Dermatology Online Journal, 2016)
Eosinophilic pustular folliculitis or Ofuji's disease is a non-infectious eosinophilic infiltration of hair follicles, which usually presents with itchy papules and pustules in a circinate configuration. We report this case of an immunocompetent patient with erythematous papules and plaques without macropustules diagnosed as eosinophilic pustular folliculitis—a rarely reported entity outside Japan. He was successfully treated with oral dapsone.